Cohort profile: prescriptions dispensed in the community linked to the national cancer registry in England. Issue 7 (10th July 2018) - Henson, Katherine E; Brock, Rachael; Shand, Brian; Coupland, Victoria H; Elliss-Brookes, Lucy; Lyratzopoulos, Georgios; Godfrey, Philip; Haigh, Abigail; Hunter, Kelvin; McCabe, Martin G; Mitchell, Graham; Monckton, Nina; et al.
Abstract : Purpose: The linked prescriptions cancer registry data resource was set up to extend our understanding of the pathway for patients with cancer past secondary care into the community, to ultimately improve patient outcomes. Participants: The linked prescriptions cancer registry data resource is currently available for April to July 2015, for all patients diagnosed with cancer in England with a dispensed prescription in that time frame. The dispensed prescriptions data are collected by National Health Service (NHS) Prescription Services, and the cancer registry data are processed by Public Health England. All data are routine healthcare data, used for secondary purposes, linked using a pseudonymised version of the patient's NHS number and date of birth. Detailed demographic and clinical information on the type of cancer diagnosed and treatment is collected by the cancer registry. The dispensed prescriptions data contain basic demographic information, geography measures of the dispensed prescription, drug information (quantity, strength and presentation), cost of the drug and the date that the dispensed prescription was submitted to NHS Business Services Authority. Findings to date: Findings include a study of end of life prescribing in the community among patients with cancer, an investigation of repeat prescriptions to derive measures of prior morbidity status in patients with cancer and studies of prescription activity surrounding the date of cancer diagnosis. Future plans: This English linked resource could be used for cancer epidemiological studies of diagnostic pathways, health outcomes and inequalities; to establish primary care comorbidity indices and for guideline concordance studies of treatment, particularly hormonal therapy, as a major treatment modality for breast and prostate cancer which has been largely delivered in the community setting for a number of years.